2013
DOI: 10.1074/jbc.m113.468405
|View full text |Cite
|
Sign up to set email alerts
|

Lipids as Tumoricidal Components of Human α-Lactalbumin Made Lethal to Tumor Cells (HAMLET)

Abstract: Background: HAMLET is a broadly tumoricidal complex of partially unfolded ␣-lactalbumin and oleic acid whose structural and functional contributions to HAMLET remain largely undefined. Results:The protonation state and function of the lipid are elucidated. Conclusion: HAMLET and oleate possess unique and overlapping effects on tumor cells. Significance: Unfolded proteins, like ␣-lactalbumin, form novel functional entities with deprotonated fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…While we have no definite explanation for the discrepancy, poor solubility of OA, its tendency to stick to the walls of plastic tubes under the conditions of the study and consequent low availability [17] for interacting with the cells apparently necessitated high concentrations of the fatty acid to induce hemolysis. Oleate, that forms HAMLET-like complexes [41] and its relevant constituent [42], was however more hemolytic than OA and moderately more hemolytic than even α-LA associated OA (Figure 2B). BAMLET prepared by the procedure of Kamijima et al [20], when subjected to crosslinking with 0.01% glutaraldehyde resulted in the formation of adducts that moved in SDS-PAGE as polypeptides ranging from 50 kDa to those that were too large to enter the gel (Figure S2) as also reported by Spolaore et al [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have no definite explanation for the discrepancy, poor solubility of OA, its tendency to stick to the walls of plastic tubes under the conditions of the study and consequent low availability [17] for interacting with the cells apparently necessitated high concentrations of the fatty acid to induce hemolysis. Oleate, that forms HAMLET-like complexes [41] and its relevant constituent [42], was however more hemolytic than OA and moderately more hemolytic than even α-LA associated OA (Figure 2B). BAMLET prepared by the procedure of Kamijima et al [20], when subjected to crosslinking with 0.01% glutaraldehyde resulted in the formation of adducts that moved in SDS-PAGE as polypeptides ranging from 50 kDa to those that were too large to enter the gel (Figure S2) as also reported by Spolaore et al [19].…”
Section: Resultsmentioning
confidence: 99%
“…During their investigation of HAMLET-induced ion channels in A549 lung carcinoma cells, Storm et al [43] observed that the increase in free intracellular calcium was not restricted by inclusion of EGTA in the medium but by the inhibition of INsP3-gated ER Ca 2+ channel with U73122, implying that it originated mainly from intracellular stores. In another recent study [42] it was however shown that HAMLET and oleate trigger overlapping but fundamentally different responses on the ion channels of the lung carcinoma and Jurkat cells.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, some further restrictions are placed on the culture chambers used, as normal cell culture at these time scales requires regular change of the cell culture medium. Consequently, long term studies have used various kinds of perfusion chambers to be able to replace the medium without disturbing the imaging view [30,32,39,43,49,55,61]. Several studies have also used larger culture chambers with large enough volume to avoid changing the medium entirely, such as by using a T25 cell culture flask (Table 1).…”
Section: Choice Of Cell Culture and Imaging Vesselmentioning
confidence: 99%
“…As monitored by DH, 15 min of incubation, with 35 μM of HAMLET, was enough for a reduction in cell area and increase in thickness, with evidence of membrane blebbing in human lung carcinoma A549 cells [26]. After 60 min, the cells became even smaller in area and thicker [30]. Puthia et al examined how HAMLET affects β-catenin and Wnt-signaling in the treated human colon cancer cell line DLD1.…”
Section: Cell Death Of Adherent Cellsmentioning
confidence: 99%